Easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane and preparation method thereof

Through the double-layer mouth molding technology and the method of synchronous extrusion of the material liquid by synchronously extruding the material liquid by the twin-screw extruder, a polyvinylidene fluoride hollow fiber membrane with different pore sizes was prepared, which solved the problem of the existing film being easily stained and blocked but not easy to clean, and improved the The service life and strength of the membrane.

CN116726738BActive Publication Date: 2025-02-11SHANDONG ZHAOJIN MOTIAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310896002.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-02-11
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

The polyvinylidene fluoride hollow fiber membrane prepared by the existing thermal phase separation method has a single pore structure, which is easy to be blocked and difficult to clean, affecting its service life.

Method used

Using double-layer mouth molding technology, the inner layer membrane structure and outer layer membrane structure are synchronously extruded through two twin-screw extruders to form an outer inner layer structure with different pore diameters, and the inner layer pore diameter is larger than the outer layer pore diameter.

Benefits of technology

It effectively avoids the problem of difficult cleaning of membrane products after being blocked, ensures the service life of the membrane, and improves the strength of the membrane and the uniformity of the pore structure through the use of modified masterbatches.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure, which includes an outer membrane structure and an inner membrane structure, both of which are prepared by a thermo-induced phase spinning process, and are synchronously extruded by two twin-screw extruders and respectively formed by two layers of dies, wherein the pore structures of the outer membrane structure and the inner membrane structure have different pore diameters, and the pore diameter of the pore structure of the inner membrane structure is larger than that of the pore structure of the outer membrane structure. The present invention also provides a method for preparing a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure. The present invention uses the same thermo-induced phase membrane making process to ensure the effective combination of the inner membrane raw material and the outer membrane raw material from the source, avoid the membrane stratification problem, and the pore diameter is adjustable; and the present invention changes the structural morphology of the hollow fiber membrane with a single pore structure in the past, and effectively avoids the problem of the membrane product being difficult to clean after being blocked during operation by forming two layers of pore structures with uniform size and filter pore diameters that increase from small to large from the outside to the inside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure and a preparation method thereof. Background Art

[0002] Membrane separation technology is one of the separation technologies that has developed rapidly in the past 30 years. At the same time, due to its strong controllability of separation accuracy, good and stable separation effect, it is widely used in various aspects such as deep sewage treatment and medical materials.

[0003] Polyvinylidene fluoride has outstanding chemical resistance, high temperature resistance, and stable properties, which provides a variety of processing options. Therefore, polyvinylidene fluoride is the main raw material for ultra-fine filtration membranes. However, ultra-fine filtration membranes with uniform pore size have problems with microbial contamination and post-contamination cleaning and recovery during use.

[0004] There are two main preparation technology systems for polyvinylidene fluoride hollow fiber membranes: one is a method based on the principle of non-solvent induced phase separation. This method requires simple equipment and has a low processing temperature. It is also convenient to add various modification additives and easily form different pore structures. However, the membranes prepared by this method are often of low strength, thin functional cortex, easy to damage, and often have a short service life. The other is a thermally induced phase separation method, which utilizes the characteristics of high temperature compatibility and low temperature phase separation of resin and diluent to prepare a homogeneous porous membrane. The membranes prepared by this method have the characteristics of high strength, good chemical resistance, and uniform pore size, which greatly improves the service life of the membrane. Therefore, the thermally induced phase separation method has gradually become the leading preparation technology for the new generation of PVDF porous membranes.

[0005] However, although the hollow fiber membrane products prepared by the thermally induced phase separation method have excellent physical and chemical properties, the current thermally induced phase membrane making process mostly uses a single-layer membrane pore structure membrane with uniform pore size, which is easy to be blocked during use and difficult to clean after being blocked, which ultimately affects the service life of the membrane. Some people have also tried to add non-solvent phase membrane liquid to the outside of the thermally induced phase membrane pores to make up for the problem of insufficient single pore size, but because it is a composite of two different membrane making processes, there is a problem of weak adhesion leading to stratification, and this attempt cannot guarantee the quality and service life of the membrane fibers.

[0006] The inventors of the present application have also tried to compensate for the single pore size problem by coating the surface of a single-layer membrane pore structure membrane with a thermotropic high-temperature molten raw material after the membrane is formed. However, since the two layers of liquid are not formed synchronously, the post-coating liquid clogs the original single-layer pore structure and causes uneven coating, making it impossible to effectively control the pore structure size and ensure the quality of the membrane fibers. Summary of the invention

[0007] In view of the above-mentioned deficiencies in the prior art, it would be advantageous to provide a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure and a preparation method thereof.

[0008] To this end, according to the first aspect of the present invention, there is provided an easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane, which includes an outer membrane structure and an inner membrane structure, both of which are prepared by a thermophase spinning process, extruded synchronously by two twin-screw extruders, and formed by two layers of dies, wherein the pore structures of the outer membrane structure and the inner membrane structure have different pore diameters, and the pore structure of the inner membrane structure has a larger pore diameter than that of the pore structure of the outer membrane structure.

[0009] Furthermore, the liquid composition of the inner layer membrane structure is: modified masterbatch, polyvinylidene fluoride resin and organic liquid, and the weight ratio of the three is controlled in the range of 1:1:1 to 1:1:2, wherein the modified masterbatch includes, by weight percentage:

[0010] Polyvinylidene fluoride: 10~15%;

[0011] Nano calcium carbonate: 50~60%;

[0012] High molecular weight antibacterial agent: 20~30%;

[0013] Modified additives: 1~5%;

[0014] In addition, the liquid composition of the outer membrane structure is: modified masterbatch, polyvinylidene fluoride resin and organic liquid, and the weight ratio of the three is controlled in the range of 1:1:1 to 1:1:3; wherein the modified masterbatch includes, by weight percentage:

[0015] Polyvinylidene fluoride: 15~25%;

[0016] Nano calcium carbonate: 45~50%;

[0017] High molecular weight antibacterial agent: 20~34%;

[0018] Modified additives: 1~5%.

[0019] Furthermore, the liquid material of the inner layer membrane structure is melt-mixed and extruded through a twin-screw extruder at 180-230°C;

[0020] The liquid material of the outer membrane structure is melt-mixed and extruded through a twin-screw extruder at 200-230°C;

[0021] The slurry of the inner membrane structure and the slurry of the outer membrane structure are extruded by two twin-screw extruders and then sprayed out from the two-layer die through a metering pump. After cooling, forming and stretching 1.5 to 2.5 times, the organic liquid and nano-calcium carbonate in the inner membrane structure and the outer membrane structure are extracted to prepare a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure.

[0022] Furthermore, the polyvinylidene fluoride is a high molecular weight polyvinylidene fluoride, preferably a vinylidene fluoride homopolymer, and has a melt flow rate (MFR) of 1 to 4 g / 10 min (230° C. / 21.6 kg).

[0023] Furthermore, the organic liquid is selected from synthetic plant esters, citrate esters, adipate esters, and soybean oil.

[0024] Furthermore, the nano calcium carbonate is quasi-cubic in shape, and has an average particle size of 20 to 150 nanometers.

[0025] Furthermore, the high molecular weight antibacterial agent is one or a mixture of polyhexamethylene guanidine (PHMG), polyhexamethylene biguanide (PHMB), chitosan and their derivatives with a weight average molecular weight greater than 20,000.

[0026] Furthermore, the polymer antibacterial agent is preferably a liquid preparation containing 25-50% of the above-mentioned active ingredient.

[0027] Furthermore, the modified additive is a high temperature resistant surfactant, which is mainly used to improve the wetting and adsorption effect of nano calcium carbonate and polymer antibacterial agent preparations.

[0028] Furthermore, the modifying additive is preferably an organic fluorine surfactant solution, such as perfluorosulfonate or perfluorocarboxylic acid.

[0029] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane, which comprises the following steps:

[0030] (1) preparing a modified masterbatch in the inner layer film structure liquid by mixing and extruding, wherein the modified masterbatch comprises, by weight percentage:

[0031] Polyvinylidene fluoride: 10~15%;

[0032] Nano calcium carbonate: 50~60%;

[0033] High molecular weight antibacterial agent: 20~30%;

[0034] Modified additives: 1~5%;

[0035] (2) preparing a modified masterbatch in the outer film structure liquid by mixing and extruding, wherein the modified masterbatch comprises, by weight percentage:

[0036] Polyvinylidene fluoride: 15~25%;

[0037] Nano calcium carbonate: 45~50%;

[0038] High molecular weight antibacterial agent: 20~34%;

[0039] Modified additives: 1~5%;

[0040] (3) preparing and homogenizing an inner layer membrane structure feed liquid, wherein the inner layer membrane structure feed liquid includes a modified masterbatch, a polyvinylidene fluoride resin, and an organic liquid in a weight ratio controlled within a range of 1:1:1 to 1:1:2;

[0041] (4) preparing and homogenizing an outer membrane structure liquid, wherein the outer membrane structure liquid comprises a modified masterbatch, a polyvinylidene fluoride resin, and an organic liquid in a weight ratio controlled within a range of 1:1:1 to 1:1:3;

[0042] (5) The homogenized inner layer membrane structure liquid and the outer layer membrane structure liquid are continuously and simultaneously extruded by two twin-screw extruders, and are synchronously sprayed out from two-layer dies after passing through a metering pump. After cooling and forming and stretching 1.5 to 2.5 times, the organic liquid and nano-calcium carbonate are extracted to prepare an easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane;

[0043] The liquid material of the inner layer membrane structure is melt-mixed and extruded through a twin-screw extruder at 180-230° C.; the liquid material of the outer layer membrane structure is melt-mixed and extruded through a twin-screw extruder at 200-230° C.

[0044] Further, the preparation of the modified masterbatch comprises the following steps:

[0045] 1) Pass the nano calcium carbonate through a 325 mesh mechanical sieve to eliminate large soft agglomerates;

[0046] 2) Adding nano calcium carbonate and modified additives into a high-speed mixer for surface pretreatment;

[0047] 3) Add the pretreated nano-calcium carbonate and polymer antibacterial agent into the stirring tank, stir at high speed, and disperse with ultrasonic waves for 10 to 50 minutes;

[0048] 4) Add polyvinylidene fluoride and stir for 30 minutes, then mix through a twin-screw extruder at a mixing temperature of 180-200°C. At the same time, multi-stage vacuuming is used to discharge the volatile matter, and the vacuum degree is -0.2-0.8 bar. Then extrude the mixture, water-cool or air-cooled pelletize, and remove the surface floating water to obtain the modified masterbatch.

[0049] Furthermore, when water cooling is used, the water cooling temperature is controlled at 15~35℃, and the water-cooled particles are dried at 80℃; when air cooling is used, air cooling is performed at room temperature, and the wind speed is matched according to the output.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] 1) Compared with the traditional thermally induced phase separation method, the present invention changes the single pore structure of the hollow fiber membrane in the past by simultaneously forming an outer membrane structure and an inner membrane structure with pore structures of different sizes. That is, by forming a hollow fiber membrane structure with two layers of uniform size and pore structures with filtration pores that increase from small to large from the outside to the inside, the problem of the membrane product being difficult to clean after being blocked during operation is effectively avoided;

[0052] 2) The present invention uses the same thermo-induced phase membrane making process to ensure the effective combination of the inner membrane material and the outer membrane material from the source, avoiding the membrane stratification problem, extracting the organic liquid and nano-calcium carbonate after cooling and forming, and preparing a hollow fiber membrane with two layers of membrane structure with different pore sizes;

[0053] 3) The present invention uses two twin-screw extruders to extrude simultaneously, and is ejected synchronously through a metering pump and two-layer dies. The operation is convenient, and it is beneficial to adjust the raw material ratio of each layer of the membrane structure and the corresponding extrusion process (such as mixing temperature), effectively ensuring the size of the formed membrane pore structure, and the pore diameter can be adjusted according to needs;

[0054] 4) The modified masterbatch prepared by the present invention is a highly dispersed body with nano calcium carbonate as a carrier. The modified masterbatch is directly added to a twin-screw extruder with a matrix polyvinylidene fluoride resin, an organic liquid, etc. in a proportionate and continuous weight ratio, and a polyvinylidene fluoride hollow fiber membrane is prepared by a thermally induced phase separation method. Compared with the traditional direct blending thermally induced phase separation method for preparing porous membranes, the film preparation continuity is stronger and more convenient for large-scale expansion. At the same time, some substances that cannot be directly added to the blending system can be selected in the final film preparation formula, which greatly expands the selectivity of the formula ingredients and expands the diversity of the modification direction of the porous membrane prepared by the thermally induced phase separation method.

[0055] 5) The high molecular weight polyvinylidene fluoride resin used in the present invention is a masterbatch molding support matrix resin. When added to a conventional polyvinylidene fluoride resin suitable for thermally induced phase separation membrane preparation for mixing and membrane preparation, the modified masterbatch and the polyvinylidene fluoride resin are well compatible, and the strength of the porous membrane can be improved without affecting the pore-forming performance.

[0056] These and other aspects of the invention will be more clearly elucidated with reference to the embodiments described hereinafter. DETAILED DESCRIPTION

[0057] The present invention will be described in detail below with reference to the embodiments. Embodiment 1

[0058] 1) Preparation of modified masterbatch for inner layer membrane structure liquid: Grind the nano calcium carbonate to pass through a 325 mesh screen, then add the ground and sieved powder into a high-speed mixer, add the perfluorosulfonate solution as a modified additive into the nano calcium carbonate in the form of spray while stirring, and stir at high speed for 10 minutes; then move the pretreated powder into an ultrasonic processor with high-speed stirring, add PHMG (PH) (i.e. polyhexamethylene guanidine phosphate, a derivative of polyhexamethylene guanidine) aqueous solution, stir for 20 minutes under 30KHZ ultrasonic conditions, then add high molecular weight polyvinylidene fluoride powder with an MFR of 2.0g / 10min (230℃, 21.6kg), and stir evenly; then introduce the mixture into a twin-screw extruder, mix at 195℃, and simultaneously evacuate the small molecular volatiles (i.e. water vapor and low boiling point substances) through multi-stage vacuuming, with a vacuum degree of -0.3~-0.7bar.

[0059] The weight percentages of the components of the modified masterbatch prepared above are as follows:

[0060] High molecular weight polyvinylidene fluoride: 10%

[0061] Nano calcium carbonate: 60%

[0062] PHMG (PH) aqueous solution: 29%

[0063] Perfluorosulfonate solution: 1%

[0064] 2) Compare the above method for preparing modified masterbatch for inner layer membrane structure liquid to prepare modified masterbatch for outer layer membrane structure liquid: introduce the mixture into another twin-screw extruder, mix at 210°C, and simultaneously perform multi-stage vacuum to discharge small molecule volatiles (i.e. water vapor and low boiling point substances), with a vacuum degree of -0.5~-0.8bar.

[0065] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0066] High molecular weight polyvinylidene fluoride: 25%

[0067] Nano calcium carbonate: 45%

[0068] PHMG (PH) aqueous solution: 25%

[0069] Perfluorosulfonate solution: 5%

[0070] 3) Preparation of easy-to-clean porous structure polyvinylidene fluoride hollow fiber membrane: using a twin-screw extruder connected with a metering pump system, the modified masterbatch of the inner layer membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate are added to the twin-screw extruder in a ratio of 1:1:1.5 by weight feeding, and after mixing at 195°C, they are extruded through one of the two-layer annular die (a membrane wire forming die); at the same time, using a twin-screw extruder connected with a metering pump system, the modified masterbatch in the outer layer membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate are mixed in a ratio of 1:1:2. The proportion is added to the twin-screw extruder by weight feeding, and after mixing at 210°C, the other layer is extruded through the annular two-layer die; the inner membrane structure liquid and the outer membrane structure liquid are extruded synchronously, and synchronously cooled to form a hollow fiber membrane, which is then stretched 2 times, and then the organic solvent and nano-calcium carbonate are extracted with ethanol and hydrochloric acid. During the entire thermotropic spinning process (i.e., the molding process), the two layers of liquid flow stably, and the pore size changes from small to large from the outside to the inside (i.e., the pore size of the two layers is different, while the pore size of each layer is uniform), thereby obtaining a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure.

[0071] 4) Performance test: The prepared easy-to-clean porous structure polyvinylidene fluoride hollow fiber membrane has a pure water flux of 900L / (㎡*h) at 25°C and 0.1Mpa, a tensile breaking strength of 15Mpa, and an elongation at break of 100%. The maximum pore size of the inner layer measured by the bubble pressure method is 0.2um, the maximum pore size of the outer layer is 0.1um, and the porosity is 79%. In addition, no obvious connection marks between the inner and outer layers can be seen through the electron microscope structure photos, and the integration is obvious. Embodiment 2

[0072] 1) Preparation of modified masterbatch for inner membrane structure liquid: Grind the nano calcium carbonate to pass through a 325 mesh screen, then add the ground and sieved powder into a high-speed mixer, add the perfluorocarboxylic acid solution into the nano calcium carbonate in the form of a spray while stirring, and stir at high speed for 10 minutes; then move the pretreated powder into an ultrasonic processor with high-speed stirring, add a carboxymethyl chitosan aqueous agent, stir at 30KHZ for 20 minutes, then add a high molecular weight polyvinylidene fluoride powder with an MFR of 2.0g / 10min (230℃, 21.6kg), and stir evenly; then introduce the mixture into a twin-screw extruder, mix at 180℃, and simultaneously evacuate the small molecular volatiles (i.e., water vapor and low-boiling point substances) through multi-stage vacuum, with a vacuum degree of -0.4~-0.7bar.

[0073] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0074] High molecular weight polyvinylidene fluoride: 15%

[0075] Nano calcium carbonate: 50%

[0076] Carboxymethyl chitosan aqueous solution: 30%

[0077] Perfluorocarboxylic acid solution: 5%

[0078] 2) In contrast to the above method for preparing the modified masterbatch for the inner layer membrane structure liquid, the modified masterbatch for the outer layer membrane structure liquid is prepared: the mixture is introduced into another twin-screw extruder, mixed at 200°C, and at the same time, multi-stage vacuuming is performed to discharge small molecular volatiles (i.e., water vapor and low-boiling point substances), and the vacuum degree is -0.5~-0.8bar.

[0079] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0080] High molecular weight polyvinylidene fluoride: 15%

[0081] Nano calcium carbonate: 50%

[0082] Carboxymethyl chitosan aqueous solution: 34%

[0083] Perfluorocarboxylic acid solution: 1%

[0084] 3) Preparation of easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane: Use a twin-screw extruder connected with a metering pump system to feed the modified masterbatch of the inner layer membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate in a ratio of 1:1:2 into the twin-screw extruder by weight feeding, mix at 180°C and extrude through one of the two-layer annular die; Use a twin-screw extruder connected with a metering pump system to feed the modified masterbatch of the outer layer membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate in a ratio of 1:1:3. The material is fed by weight into a twin-screw extruder, mixed at 200°C and extruded through a two-layer annular die. The inner membrane structure liquid and the outer membrane structure liquid are extruded synchronously and cooled synchronously to form a hollow fiber membrane, which is then stretched 2 times. The organic solvent and nano-calcium carbonate are extracted with ethanol and hydrochloric acid. During the entire thermo-induced phase spinning process, the two layers of liquid flow stably, and the pore size increases from small to large from the outside to the inside (i.e., the pore size of the two layers is different, while the pore size of each layer is uniform), thereby obtaining a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure.

[0085] 4) Performance test: The prepared easy-to-clean porous structure polyvinylidene fluoride hollow fiber membrane has a pure water flux of 1000L / (㎡*h) at 25℃ and 0.1Mpa, a tensile breaking strength of 14Mpa, and an elongation at break of 120%. The maximum pore size of the inner layer measured by the bubble pressure method is 0.25um, the maximum pore size of the outer layer is 0.15um, and the porosity is 80%. In addition, no obvious connection marks between the inner and outer layers can be seen through the electron microscope structure photos, and the integration is obvious. Embodiment 3

[0086] 1) Preparation of modified masterbatch for inner membrane structure liquid: Grind the nano calcium carbonate to pass through a 325 mesh screen, then add the ground and sieved powder into a high-speed mixer, add the perfluorocarboxylic acid solution into the nano calcium carbonate in the form of spray while stirring, and stir at high speed for 10 minutes; then move the pretreated powder into an ultrasonic processor with high-speed stirring, add PHMG (GL) (i.e. polyhexamethylene guanidine gluconate, a derivative of polyhexamethylene guanidine) aqueous solution, stir at 30KHZ for 20 minutes, then add high molecular weight polyvinylidene fluoride powder with an MFR of 2.0g / 10min (230℃, 21.6kg), and stir evenly; then introduce the mixture into a twin-screw extruder, mix at 200℃, and simultaneously evacuate the small molecular volatiles (i.e. water vapor and low boiling point substances) by multi-stage vacuuming, and the vacuum degree is -0.5~-0.8bar.

[0087] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0088] High molecular weight polyvinylidene fluoride: 15%

[0089] Nano calcium carbonate: 55%

[0090] PHMG (GL) aqueous solution: 25%

[0091] Perfluorocarboxylic acid solution: 5%

[0092] 2) In contrast to the above method for preparing the modified masterbatch for the inner layer membrane structure liquid, the modified masterbatch for the outer layer membrane structure liquid is prepared: the mixture is introduced into another twin-screw extruder, kneaded at 210°C, and at the same time, multi-stage vacuuming is performed to discharge small molecular volatiles (i.e., water vapor and low-boiling point substances), and the vacuum degree is -0.4~-0.7bar.

[0093] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0094] High molecular weight polyvinylidene fluoride: 25%

[0095] Nano calcium carbonate: 50%

[0096] PHMG (GL) aqueous solution: 20%

[0097] Perfluorocarboxylic acid solution: 5%

[0098] 3) Preparation of easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane: using a twin-screw extruder connected with a metering pump system, the modified masterbatch of the upper inner membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate are added to the twin-screw extruder in a ratio of 1:1:1 by weight feeding, and after mixing at 200°C, they are extruded through one of the two-layer annular dies; using a twin-screw extruder connected with a metering pump system, the modified masterbatch in the upper outer membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate are added in a ratio of 1:1:2 by weight feeding. The material is added into a twin-screw extruder in a re-feeding manner, and after kneading at 210°C, the other layer is extruded through a two-layer annular die; the inner membrane structure liquid and the outer membrane structure liquid are extruded synchronously, and synchronously cooled to form a hollow fiber membrane, which is then stretched 2.5 times, and then ethanol and hydrochloric acid are used to extract the organic solvent and nano-calcium carbonate. During the entire thermo-induced phase spinning process, the two layers of liquid flow stably, and the pore size changes from small to large from the outside to the inside (that is, the pore size of the two layers is different, while the pore size of each layer is uniform), thereby obtaining a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure.

[0099] 4) Performance test: The prepared easy-to-clean porous structure polyvinylidene fluoride hollow fiber membrane has a pure water flux of 1300L / (㎡*h) at 25°C and 0.1Mpa, a tensile breaking strength of 16Mpa, and an elongation at break of 110%. The maximum pore size of the inner layer measured by the bubble pressure method is 0.15um, the maximum pore size of the outer layer is 0.10um, and the porosity is 78%. In addition, no obvious connection marks between the inner and outer layers can be seen through the electron microscope structure photos, and the integration is obvious. Embodiment 4

[0100] 1) Preparation of modified masterbatch for inner membrane structure liquid: Grind the nano calcium carbonate to pass through a 325 mesh screen, then add the ground and sieved powder into a high-speed mixer, add the perfluorosulfonate solution into the nano calcium carbonate in the form of a spray while stirring, and stir at high speed for 10 minutes; then move the pretreated powder into an ultrasonic processor with high-speed stirring, add carboxymethyl chitosan aqueous agent, stir at 30KHZ for 20 minutes, then add high molecular weight polyvinylidene fluoride powder with an MFR of 2.0g / 10min (230℃, 21.6kg), and stir evenly; then introduce the mixture into a twin-screw extruder, mix at 220℃, and simultaneously vacuumize to discharge small molecular volatiles by multi-stage vacuum, with a vacuum degree of -0.4~-0.7bar.

[0101] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0102] High molecular weight polyvinylidene fluoride: 15%

[0103] Nano calcium carbonate: 60%

[0104] Carboxymethyl chitosan aqueous solution: 20%

[0105] Perfluorosulfonate solution: 5%

[0106] 2) In contrast to the above method for preparing the modified masterbatch for the inner layer membrane structure liquid, the modified masterbatch for the outer layer membrane structure liquid is prepared: the mixture is introduced into another twin-screw extruder, kneaded at 230°C, and at the same time, multi-stage vacuuming is performed to discharge small molecular volatiles (i.e., water vapor and low-boiling point substances), and the vacuum degree is -0.5~-0.9bar.

[0107] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0108] High molecular weight polyvinylidene fluoride: 20%

[0109] Nano calcium carbonate: 50%

[0110] Carboxymethyl chitosan aqueous solution: 28%

[0111] Perfluorosulfonate solution: 2%

[0112] 3) Preparation of easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane: Using a twin-screw extruder connected with a metering pump system, the modified masterbatch of the inner layer membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate are added to the twin-screw extruder in a ratio of 1:1:1.5 by weight feeding, and after mixing at 220°C, they are extruded through one of the two-layer annular dies; using a twin-screw extruder connected with a metering pump system, the modified masterbatch in the outer layer membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate are added in a ratio of 1:1:2 by weight feeding. The material is fed by weight into a twin-screw extruder, mixed at 230°C, and extruded through a two-layer annular die. The inner membrane structure liquid and the outer membrane structure liquid are extruded synchronously and cooled synchronously to form a hollow fiber membrane, which is then stretched 1.5 times. The organic solvent and nano-calcium carbonate are extracted with ethanol and hydrochloric acid. During the entire thermotropic spinning process, the two layers of liquid flow stably, and the pore size increases from small to large from the outside to the inside (i.e., the pore size of the two layers is different, while the pore size of each layer is uniform), thereby obtaining a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure.

[0113] 4) Performance test: The pure water flux of the prepared easy-to-clean porous structure polyvinylidene fluoride hollow fiber membrane at 25°C and 0.1Mpa is 980L / (㎡*h), the tensile strength is 15Mpa, the elongation at break is 100%, and the maximum pore size of the inner layer measured by the bubble pressure method is 0.18um, the maximum pore size of the outer layer is 0.10um, the porosity is 73%, and there is no obvious connection between the inner and outer layers through the electron microscope structure photos, and the integration is obvious. Embodiment 5

[0114] 1) Preparation of modified masterbatch for inner membrane structure liquid: Grind the nano calcium carbonate to pass through a 325 mesh screen, then add the ground and sieved powder into a high-speed mixer, add the perfluorosulfonate solution into the nano calcium carbonate in the form of a spray while stirring, and stir at high speed for 10 minutes; then move the pretreated powder into an ultrasonic processor with high-speed stirring, add PHMG (GL) aqueous agent, stir at 30KHZ for 20 minutes, then add high molecular weight polyvinylidene fluoride powder with an MFR of 2.0g / 10min (230℃, 21.6kg), and stir evenly; then introduce the mixture into a twin-screw extruder, mix at 230℃, and simultaneously vacuumize to discharge small molecular volatiles by multi-stage vacuum, with a vacuum degree of -0.4~-0.7bar.

[0115] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0116] High molecular weight polyvinylidene fluoride: 12.5%

[0117] Nano calcium carbonate: 60%

[0118] PHMG (GL) aqueous solution: 24.5%

[0119] Perfluorosulfonate solution: 3%

[0120] 2) In contrast to the above method for preparing the modified masterbatch for the inner layer membrane structure liquid, the modified masterbatch for the outer layer membrane structure liquid is prepared: the mixture is introduced into another twin-screw extruder, kneaded at 230°C, and at the same time, multi-stage vacuuming is performed to discharge small molecular volatiles (i.e., water vapor and low-boiling point substances), and the vacuum degree is -0.5~-0.9bar.

[0121] The weight percentages of the components of the prepared modified masterbatch are as follows:

[0122] High molecular weight polyvinylidene fluoride: 25%

[0123] Nano calcium carbonate: 45%

[0124] PHMG (GL) aqueous solution: 28%

[0125] Perfluorosulfonate solution: 2%

[0126] 3) Preparation of easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane: using a twin-screw extruder connected with a metering pump system, the modified masterbatch of the upper inner membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate are added to the twin-screw extruder in a ratio of 1:1:1.5 by weight feeding, and after mixing at 230°C, they are extruded through one of the two-layer annular dies; using a twin-screw extruder connected with a metering pump system, the modified masterbatch in the upper outer membrane structure liquid, polyvinylidene fluoride powder, and triethyl citrate are added in a ratio of 1:1:1. The material is fed by weight into a twin-screw extruder, mixed at 230°C and extruded through a two-layer annular die, and the other layer is extruded; the inner membrane structure liquid and the outer membrane structure liquid are extruded synchronously, and cooled synchronously to form a hollow fiber membrane, which is then stretched 2 times, and then the organic solvent and nano-calcium carbonate are extracted with ethanol and hydrochloric acid. During the entire thermophase spinning process, the two layers of liquid flow stably, and the pore size increases from small to large from the outside to the inside (that is, the pore size of the two layers is different, while the pore size of each layer is uniform), thereby obtaining a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure.

[0127] 4) Performance test: The pure water flux of the prepared easy-to-clean porous structure polyvinylidene fluoride hollow fiber membrane at 25°C and 0.1Mpa is 880L / (㎡*h), the tensile strength at break is 13Mpa, the elongation at break is 120%, and the maximum pore size of the inner layer measured by the bubble pressure method is 0.16um, the maximum pore size of the outer layer is 0.11um, the porosity is 75%, and no obvious connection marks between the inner and outer layers can be seen through the electron microscope structure photos, and the integration is obvious.

[0128] The technical content and technical features of the present invention have been disclosed above, but it is understood that under the creative ideas of the present invention, those skilled in the art can make various changes and improvements to the above components and steps, including combinations of technical features disclosed or claimed separately here, and other combinations that obviously include these features. These variations and / or combinations all fall within the technical field involved in the present invention and fall within the protection scope of the claims of the present invention.

Claims

1. An easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane, characterized in that The outer membrane structure and the inner membrane structure are prepared by a thermophase spinning process, and are extruded synchronously by two twin-screw extruders and formed by two dies. The pore structures of the outer membrane structure and the inner membrane structure have different pore diameters, and the pore diameter of the pore structure of the inner membrane structure is larger than that of the pore structure of the outer membrane structure. The liquid composition of the inner membrane structure is: modified masterbatch, polyvinylidene fluoride resin and organic liquid, and the weight ratio of the three is controlled in the range of 1:1:1 to 1:1:2, wherein the modified masterbatch includes, by weight percentage: Polyvinylidene fluoride: 10~15%; Nano calcium carbonate: 50~60%; High molecular weight antibacterial agent: 20~30%; Modified additives: 1~5%; Furthermore, the liquid composition of the outer membrane structure is: modified masterbatch, polyvinylidene fluoride resin and organic liquid, and the weight ratio of the three is controlled within the range of 1:1:1 to 1:1:3; wherein the modified masterbatch includes, by weight percentage: Polyvinylidene fluoride: 15~25%; Nano calcium carbonate: 45~50%; High molecular weight antibacterial agent: 20~34%; Modified additives: 1~5%; Wherein, the organic liquid is selected from synthetic plant esters, citrate esters, adipic acid esters, and soybean oil.

2. The easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane according to claim 1, characterized in that: The liquid of the inner layer membrane structure is melt-mixed and extruded through a twin-screw extruder at 180-230°C; The outer film structure is melt-mixed and extruded through a twin-screw extruder at 200-230°C; The slurry of the inner membrane structure and the slurry of the outer membrane structure are extruded by two twin-screw extruders and then sprayed out from the two-layer die through a metering pump. After cooling, forming and stretching 1.5 to 2.5 times, the organic liquid and nano-calcium carbonate in the inner membrane structure and the outer membrane structure are extracted to prepare a polyvinylidene fluoride hollow fiber membrane with an easy-to-clean pore structure.

3. The easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane according to claim 1, characterized in that: The polyvinylidene fluoride is a high molecular weight polyvinylidene fluoride, and its melt flow rate (MFR) is 1-4 g / 10 min (230° C. / 21.6 kg).

4. The easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane according to claim 3, characterized in that: The high molecular weight polyvinylidene fluoride is a vinylidene fluoride homopolymer.

5. The easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane according to claim 1, characterized in that: The nano calcium carbonate is cubic in shape and has an average particle size of 20 to 150 nanometers.

6. The easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane according to claim 1, characterized in that: The high molecular antibacterial agent is one or a mixture of polyhexamethylene guanidine (PHMG), polyhexamethylene biguanide (PHMB), chitosan and their derivatives with a weight average molecular weight greater than 20,000.

7. The easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane according to claim 6, characterized in that: The polymer antibacterial agent is a liquid preparation with an effective ingredient of 25-50%.

8. The easy-to-clean pore structure polyvinylidene fluoride hollow fiber membrane according to claim 1, characterized in that: The modified additive is a high temperature resistant surfactant.

9. The easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane according to claim 8, characterized in that: The modified additive is an organic fluorine surfactant solution.

10. The easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane according to claim 9, characterized in that: The organic fluorine surfactant solution is perfluorosulfonate or perfluorocarboxylic acid.

11. The method for preparing the easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane according to any one of claims 1 to 10, characterized in that The steps include: (1) preparing a modified masterbatch in the inner layer film structure liquid by mixing and extruding, wherein the modified masterbatch comprises, by weight percentage: Polyvinylidene fluoride: 10~15%; Nano calcium carbonate: 50~60%; High molecular weight antibacterial agent: 20~30%; Modified additives: 1~5%; (2) preparing a modified masterbatch in the outer film structure liquid by mixing and extruding, wherein the modified masterbatch comprises, by weight percentage: Polyvinylidene fluoride: 15~25%; Nano calcium carbonate: 45~50%; High molecular weight antibacterial agent: 20~34%; Modified additives: 1~5%; (3) preparing and homogenizing an inner layer membrane structure feed liquid, wherein the inner layer membrane structure feed liquid includes a modified masterbatch, a polyvinylidene fluoride resin, and an organic liquid in a weight ratio controlled within a range of 1:1:1 to 1:1:2; (4) preparing and homogenizing an outer membrane structure liquid, wherein the outer membrane structure liquid comprises a modified masterbatch, a polyvinylidene fluoride resin, and an organic liquid in a weight ratio controlled within a range of 1:1:1 to 1:1:3; (5) The homogenized inner layer membrane structure liquid and the outer layer membrane structure liquid are continuously and simultaneously extruded by two twin-screw extruders, and are synchronously sprayed out from two-layer dies after passing through a metering pump. After cooling and forming and stretching 1.5 to 2.5 times, the organic liquid and nano-calcium carbonate are extracted to prepare an easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane; The material liquid of the inner layer membrane structure is melt-mixed and extruded through a twin-screw extruder at 180-230°C; the material liquid of the outer layer membrane structure is melt-mixed and extruded through a twin-screw extruder at 200-230°C.

12. The method for preparing the easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane according to claim 11, characterized in that: The preparation of the modified masterbatch comprises the following steps: 1) Pass the nano calcium carbonate through a 325 mesh mechanical sieve to eliminate large soft agglomerates; 2) Adding nano calcium carbonate and modified additives into a high-speed mixer for surface pretreatment; 3) Add the pretreated nano-calcium carbonate and polymer antibacterial agent into the stirring tank, stir at high speed, and disperse with ultrasonic waves for 10 to 50 minutes; 4) adding polyvinylidene fluoride and stirring for 30 minutes, mixing by a twin-screw extruder, the mixing temperature is 180-200°C, and multi-stage vacuuming is used to discharge the volatile matter, the vacuum degree is -0.2-0.8 bar, and then the mixture is extruded, water-cooled or air-cooled for pelletizing, and the surface floating water is removed to obtain the modified masterbatch.

13. The method for preparing the easily cleanable pore structure polyvinylidene fluoride hollow fiber membrane according to claim 12, characterized in that: The water cooling temperature is controlled at 15~35°C, and the water-cooled particles are dried at 80°C; the air cooling is at room temperature, and the wind speed is matched according to the output.

Citation Information

Patent Citations

  • Polyvinylidene fluoride hollow fiber membrane as well as preparation method and application thereof

    CN114618322A

  • Bacteriostatic polyvinylidene fluoride porous membrane and preparation method thereof

    CN114806044A